„The Party of Traitors”. Research on the Institutional Malformations and Systemic Self-Regulations of Post-Communist Democracy - Dan Pavel (Sfera Politicii, 2012)
This research is based on the hypothesis that in Romania the consolidation of democracy was undermined not only at the beginning (path-dependency theory), but also at its end, in the last years. The political system seemed self-regulated, after the transition from extreme to moderate pluralism, and several turnovers, but the brutal intrusion of personalization and partisanship resulted in the fabrication of a parliamentarian pseudo-majority. With the help of a party which never participated in elections, by using blackmail, corruption and other dubious means, President Băsescu and his party ruled over Romania. The author is trying to demonstrate the self-regulatory character of democracy, by showing how a legitimate majority came to power.